EVALUATION OF SUCCESS CLAIM OF PAYMENT INFORMATION SYSTEMS AND USING DELONE MCLEAN MODEL IN HEALTHCARE - Ben Rahman (Ensiklopedia of Journal, 2019)
Abstract: The success of the system claim payment information a very active role in information systems and strategies in the core business that exists today got a critical priority for the company. The is unavoidable because of information systems has become an essential part of the survival of companies, companies that do not follow it will miss. The purpose of this study is to evaluate the billing payment systems, information systems using information systems and methods of success DeLone McLean. The analysis showed that the quality of information, quality systems, and top management support systems affect the perceived usefulness of the system. With the use of information systems claims payments affect the perceived benefits of the company is the satisfaction for users of the system in general and organizations. The perceived usefulness of the system for users is very helpful for daily operations in its work, as well as the quality of information and the quality of the system will have a direct impact to the organization, some manual processes no longer in the payment of claims to the client. With the results of this study are expected to be useful for management to determine the factors that affect the success rate of use claims payment system based on quality information and quality system. The conclusions of this evaluation are the system already meets the quality information and quality system that can further develop.